Transaksi Derivatif dalam Perspektif Hukum Islam - Imam Buchori (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
The impact of the ratification of free trade agreement is the temporary stock exchange. It is a market presenting a different trading system compared to conventional market. One of its products is derivative transaction. It is a payment contract which its value is derived from instrument value which becomes its basis, such as interest rate, exchange rate, commodity, equity and stock exchange index, either those followed by liquidity or instrument movement or otherwise. However, credit derivative transaction is not considered this derivative transaction. In Islam, there is no prohibition to conduct agreement provided that it must be executable, with good intention, and clean (free from usury, gambling, and fraudulence). An example of such an agreement is selling. As a result derivative transaction is lawful since it is in line with the principles of sharia; good objective, clean, and fulfilling the requirement of an aqd (transaction).